Using Developmental Trajectories to Understand Developmental Disorders. - Thomas, Michael S. C.; Annaz, Dagmara; Ansari, Daniel; Scerif, Gaia; Jarrold, Chris; Karmiloff-Smith, Annette (Journal of Speech, Language & Hearing Research, 2009)
Purpose: In this article, the authors present a tutorial on the use of developmental trajectories for studying language and cognitive impairments in developmental disorders and compare this method with the use of matching. Method: The authors assess the strengths, limitations, and practical implications of each method. The contrast between the methodologies is highlighted using the example of developmental delay and the criteria used to distinguish delay from atypical development. Results: The authors argue for the utility of the trajectory approach, using illustrations from studies investigating language and cognitive impairments in individuals with Williams syndrome, Down syndrome, and autism spectrum disorder. Conclusion: Two conclusions were reached: (a) An understanding of the underlying mechanism will be furthered by the richer descriptive vocabulary provided by the trajectories approach (e.g., in distinguishing different types of delay] and (b) an optimal design for studying developmental disorders is to combine initial cross-sectional designs with longitudinal follow-up. Reprinted by permission of the publisher.